On the Origin of the Commander Burundai - Seleznev Ju.V. (Золотоордынское обозрение)
Research objectives: This work focuses on the origins of Amir Buruldai (also recorded as Burundai). He was an eminent military leader of the Horde during the time of the Mongol conquests and an active participant in the seven-year-long Western campaign, defeating the main forces of the Principality of Vladimir at the Sit’ River. Research on the origin of the generals living at the time of formation of the Mongol Empire and the Golden Horde is not a simple task. Synchronous and late sources carry information mainly about the relatives of Chinggis Khan and his closest associates. Biographies of many participants of the Western campaign are reconstructed with great difficulty; almost nothing is known about them, or extremely confusing, fragmentary, and contradictory information is found. Amir Buruldai can be included among such figures, left in the shadow of Chinggis Khan, his children, and grandchildren. A famous Mongol commander, Buruldai is distinguishable in the sources during the conquest of Eastern Europe and the campaigns against Hungary and Poland. In the research literature, the figure of Burundai is given some attention. However, he is mentioned occasionally in connection with the fate and lives of Russian princes, and a complete biography or historical portrait was not made. This is largely due to the state of the source material. Its information does not give us a clear picture of one of the more illustrious generals of the time of the Mongol-Tatar conquests. At the same time, a holistic picture of the life and activities of individual military commanders during the Mongol conquests, reconstructed on the basis of written sources, can give us valuable information for generalizations about warfare waged by the Mongol Empire and the ulus of Jochi, its development in a historical perspective, and the impact on the development of weapons and warfare among neighboring countries and peoples. Research materials: The main sources of information about Burundai are epic and chronicle works of Mongolian and Chinese origin, as well as Persian and Russian chronicles. Additional and indirect information is provided by official documentation and archaeological material. Results and novelty of the research: This article concludes that among the persons mentioned in written sources, Ogelen-cherbi can be considered the most plausible figure for Boorchu’s brother. Accordingly, he is to be recognized as the father of Buraldai. The latter, in all probability, was born in about 1200.